+0  
 
+1
47
2
avatar

(x-3)(x+3)=8x

Guest Oct 17, 2017
Sort: 

2+0 Answers

 #1
avatar+8 
0

do you need help guest again

theterminat3r18  Oct 17, 2017
 #2
avatar+78719 
+2

(x-3)(x+3)=8x

 

x^2  - 9  =  8x     subtract 8x from both sides

 

x^2 - 8x - 9  = 0      factor

 

(x - 9) ( x +1)  = 0

 

Set both factors to 0

 

x - 9   =  0                                            x + 1  =  0

 

add 9 to both sides                               subtract1 from both sides

 

x =  9                                                x  =  -1

 

And those are the two solutions

 

 

cool cool cool

CPhill  Oct 17, 2017

5 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details